Imposing geometrical constraint in topology optimization for additive manufacturing - Takao MIKI; Ayumu FURUTA; Yuki SATO; Takayuki YAMADA; Kazuhiro IZUI; Shinji NISHIWAKI (Nihon Kikai Gakkai ronbunshu, 2019)
Topology optimization has been widely used in industry for designing high performance structures, but these structures are often complicated shape and cannot be manufactured directly. To solve this problem, it is necessary that geometrical constraints for manufacturability be satisfied in the optimization process. This paper proposes a scheme for imposing geometrical constraints, known as overhang constraints, in topology optimization for additive manufacturing (AM). As a feature of AM, when the inclination angle of an overhang is lower than a certain angle, AM components require temporary support materials to prevent the components from collapsing during fabrication. After the fabrication, these support materials are removed mechanically or chemically. As the use of support materials increase, manufacturing costs increase. Consequently, in order to reduce support materials, it is necessary to control the minimal inclination angle of an overhang in topology optimization. In the proposed method, the inclination angle of an overhang is represented using a fictitious physical model described by a steady-state diffusion equation. The overhang constraint can be imposed in the optimization procedure by constraining the value of the fictitious physical field. Several numerical examples are given to show the validity and effectiveness of the proposed method.